Enhancement of Neighbouring‐Group Participation in Cu0‐Promoted Cross‐Coupling gem‐Difluoromethylenation of Aryl/Alkenyl Halides with 1, 3‐Azolic Difluoromethyl Bromides. Issue 32 (2nd July 2014) - Jiang, Haizhen; Lu, Wenjun; Yang, Kun; Ma, Guobin; Xu, Minjun; Li, Jian; Yao, Jianhua; Wan, Wen; Deng, Hongmei; Wu, Shaoxiong; Zhu, Shizheng; Hao, Jian
Abstract A copper(0)‐promoted direct reductive gem‐difluoromethylenation of unactivated aryl or alkenyl halides with benzo‐1, 3‐azolic (oxa‐, thia‐ or aza‐) difluoromethyl bromides or 2‐bromodifluoromethyl‐1, 3‐oxazoline has been developed for the construction of pharmaceutically important gem‐difluoromethylene‐linked twin molecules. The unique π‐conjugated aryl‐fused 1, 3‐azolic moiety in difluoromethyl bromide substrates could stabilise the reaction intermediates, which promotes the reactivities, providing facile access to the cross‐coupling products in good to excellent yields, and allowing significant functional group tolerance. The reaction exhibits an enhanced neighbouring‐group‐participation effect. This method could provide a new strategy for the construction of gem‐difluoromethylene‐linked identical or nonidentical twin drugs through further functionalisation of 1, 3‐azolic skeletons.